PENGARUH BUDAYA KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT. CANNING INDONESIAN PRODUCTS - Antonius Pratama Angi Tukan; Ni Nyoman Suryani; I Nyoman Mustika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
This study was conducted to analyze the influence of work culture and physical work environment on the performance of employees of PT. Canning Indonesian Products. The sample in this study amounted to 61 respondents. Sampling using accidental sampling technique. The data analysis technique used is multiple linear regression. The tests carried out are model test (F), t test and classical assumptions. The results of the study prove that (1) work culture has a positive and significant effect on employee performance where if work culture is improved, employee performance will increase; (2) the physical work environment has a positive and significant effect on employee performance where if the physical work environment is improved, employee performance will increase.